Athen, Griechenland: Kerameikos - Stroszeck, Jutta (e-Forschungsberichte des DAI, 2023)
The Kerameikos excavation of the DAI’s Athens Department celebrated its 100th anniversary in 2013/2014: On 16 July 2013, a celebration at the archaeological site with speeches by the Greek Minister of Culture and Sports, Panos Panaiotopoulos (fig. 1), the DAI’s president, Friederike Fless, and others, followed by a reception marked the 100th anniversary of granting an excavation license for further research to the DAI. The actual start of the excavation was commemorated on 8 April 2014 with an international conference on sanctuaries and cults near city walls and city gates. Two research projects were carried out in 2012 and 2013. The first, started in 2011, focuses on water management in Athens. Multiple data, collected over the years at the Kerameikos excavation, help to broaden our understanding of Athenian water management within the classical city. A second project, started in 2010, has concentrated on the history of the sanctuaries at the Kerameikos. A special emphasis in 2012 and 2013 was placed on restoration and consolidation work at the site, focusing on the following monuments: the Sacred Gate, the bathhouse in front of the Dipylon, the Monument at the Third Horos, the sanctuary of Artemis Soteira / Hekate and the marvellous marble naiskos from the burial precinct of a wealthy family from Herakleia (4th cent. BC).